Cybersecurity Risk Assessment for Infrastructure of Information Systems in Yemen Telecoms - Abdulkarem Yahya Abohatem (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research paper focuses on conducting a comprehensive cybersecurity risk assessment for information systems (IS) and infrastructure within Yemen Telecoms (YT). The primary objective is to identify vulnerabilities, threats, and potential business impacts associated with cybersecurity risks. The research aims to prioritize risks, provide recommendations for risk mitigation, and highlight the importance of regular reassessments to adapt to a changing threat landscape.